The Robustness of Balinese Hindu Sacred Art in the Face of Hegel's Theory 'The Death of Art' - Fuadi, Abdulloh (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
The integration of art as an integral part of the sacred rituals of Balinese Hindu worship to this day makes the discussion of Hegel's thoughts on art is interesting. This paper attempts to discuss Hegel's theory as confronted with the sacred Balinese Hindu art. The most basic reason for the death of art is that since romantic, art has lost its subject matter. The process of dematerialisation in art gave rise to Hegel's very famous adage; the death of art. Art loses subject matter because of the limited media to express the complexity of the Absolute Spirit. However, the sacredness of Balinese Hindu art has been deeply guarded by the Balinese people. Various concepts and classifications are made to maintain its sacredness, such as the concept of belief, the concept of sekala-niskala, the concept of tri hita karana,the concept of kala patra village, the concept of karmaphala, and the concept of taksu/jengah. There is also a classification of sacred and profane arts. It is made by Balinese Hindus to maintain the sacredness of art itself. Through the art of wali and bebalih, the Balinese Hindu art maintains its subject matter concerning the complexity of the Absolute Spirit, as suggested by Hegel. Based on library research, the paper argues that the unique concept of Balinese Hindu, which may represent the wealth of indigenous religions in Indonesia, concerning sacred art can maintain its uniqueness in the global discourse arena and be able to respond creatively to contemporary challenges.